On Adam Smith's Wealth of nations : a philosophical companion - Fleischacker, Samuel (Book collections on Project MUSE., 2004)
Adam Smith was a philosopher before he ever wrote about economics, yet until now there has never been a philosophical commentary on the Wealth of Nations. Samuel Fleischacker suggests that Smith's vastly influential treatise on economics can be better understood if placed in the light of his epistemology, philosophy of science, and moral theory. He lays out the relevance of these aspects of Smith's thought to specific themes in the Wealth of Nations, arguing, among other things, that Smith regards social science as an extension of common sense rather than as a discipline to be approached mathematically, that he has moral as well as pragmatic reasons for approving of capitalism, and that he has an unusually strong belief in human equality that leads him to anticipate, if not quite endorse, the modern doctrine of distributive justice.